2015
DOI: 10.7150/jca.10865
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Targeting Cancer-Associated Fibroblasts in Melanoma

Abstract: Melanoma is known as an exceptionally aggressive and treatment-resistant human cancer. Although a great deal of progress has been made in the past decade, including the development of immunotherapy using immune checkpoint inhibitors and targeted therapy using BRAF, MEK or KIT inhibitors, treatment for unresectable stage III, stage IV, and recurrent melanoma is still challenging with limited response rate, severe side effects and poor prognosis, highlighting an urgent need for discovering and designing more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 124 publications
0
110
0
2
Order By: Relevance
“…The realization of these biological links justifies the design of clinical studies based on the targeting of CAF (and, more generally, reversal of the attributes of a protumorigenic microenvironment) in addition to targeting cancer cells in order to create a tumor-resistant environment that inhibits malignant phenotypes in diseased epithelial cells (Takebe et al 2013;Togo et al 2013;Zhou et al 2015). Such clinical studies can now be envisioned based on the findings from experimental studies with agents directed against fibroblast-specific proteins (FAP, COL11A1, and MFAP5) or signaling pathways exemplified in CAFs (TGF-β, hedgehog, Notch, FGF, PDGF, or C-X-C motif ligand 2 [CXCL2]/CXCR4 signaling).…”
Section: Acquisition Of a Caf State: Therapeutic Opportunitiesmentioning
confidence: 99%
“…The realization of these biological links justifies the design of clinical studies based on the targeting of CAF (and, more generally, reversal of the attributes of a protumorigenic microenvironment) in addition to targeting cancer cells in order to create a tumor-resistant environment that inhibits malignant phenotypes in diseased epithelial cells (Takebe et al 2013;Togo et al 2013;Zhou et al 2015). Such clinical studies can now be envisioned based on the findings from experimental studies with agents directed against fibroblast-specific proteins (FAP, COL11A1, and MFAP5) or signaling pathways exemplified in CAFs (TGF-β, hedgehog, Notch, FGF, PDGF, or C-X-C motif ligand 2 [CXCL2]/CXCR4 signaling).…”
Section: Acquisition Of a Caf State: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Functioning as the paracrine niche meanwhile, CAFs secret an important array of growth factors, including hepatic growth factor (HGF) and PDGF which bind to their specific receptors (c-MET and PDGFR respectively) on cancer cells, to activate downstream signaling kinase cascades and to consequently augment proliferation and survival of malignant cells [42,43]. CAFs can also produce CXCL12 and activate CXCR4 pathway, thereby enhancing tumor cell migration and cancer metastasis [44]. Besides, it has been found that, upon anti-cancer chemical compound treatment, CAFs strikingly up-regulate interleukine-17A (IL-17A) secretion, which is associated with promoting CSC renewal.…”
Section: Fibroblastsmentioning
confidence: 99%
“…However, exploiting this knowledge and restoring the functionality of these pathways is a daunting task. The immense progress in tumor immunology and immune therapy has shown the power of targeting nontumor cells rather than tumor cells (22).…”
Section: Cell-cell Adhesionmentioning
confidence: 99%